Innovative leadership of administrators that affects the effectiveness of educational institutions Educational Innovation Area School, Yala Province - hayideraning, awatif; Nire, Suraiya (Al-HIKMAH Journal, 2024)
The objective of this research was to study the innovative leadership level of educational institution administrators at schools in the educational innovation area, Yala Province. To study the effectiveness level of educational institutions, schools in the educational innovation area, Yala Province. To study the relationship between innovative leadership of administrators and the effectiveness of educational institutions, schools in the educational innovation area, Yala Province. and to study ways to develop the relationship between innovative leadership of administrators and the effectiveness of educational institutions. Education Innovation Area School, Yala Province The sample size was 283 people, divided into 33 school administrators and 250 teachers. The data were analyzed using the average. standard deviation and the simple Pearson correlation coefficient. The results of the research found that: 1. Innovative leadership of school administrators as a whole is at a high level ( = 4.43 , S.D. = 0.27) 2. Results of the analysis of the effectiveness level of educational institutions, educational innovation area schools, Yala Province as a whole It is at a high level ( = 4.45 , S.D. = 0.27) 3. Analysis of the relationship between innovative leadership of administrators and the effectiveness of educational institutions. Education Innovation Area School, Yala Province Using the analysis of the Pearson correlation coefficient, it was found that the innovative leadership of educational institution administrators overall (Xtot) was related to the effectiveness of educational institutions, schools, educational innovation areas, Yala Province as a whole (Ytot ) which has a high level of conformity in the relationship (rxy= .825**) with statistical significance at the .01 level. 4. Results of the study of guidelines for developing the relationship between innovative leadership of executives with the effectiveness of educational institutions Schools in the Educational Innovation Area, Yala Province, found that school administrators should be encouraged to have knowledge and understanding about innovation in management. to be used in management Including supervision, monitoring, promoting, supporting the creation and use of innovations in response to the policy and in line with the goals of developing educational institution administration driven by innovation.